Ovarian Drilling in PCOS: Is it Really Useful? - Lebbi, Issam; Ben Temime, Riadh; Fadhlaoui, Anis; Feki, Anis (Frontiers in Surgery, 2015)
Polycystic ovary syndrome (PCOS) is a frequent disorder, affecting approximately 5 to 10 % of infertile women. It can represent more than 80% of cases of infertility due to anovulation. The main goal of treatment is the induction of mono-ovulatory cycles. A pragmatic management of infertility in PCOS will allow most patients to conceive. Weight loss and clomiphene citrate (CC) are the first-line components of patients treatment before gonadotropins are used. However, during gonadotropin administration, there is a high risk of ovarian hyper-stimulation (OHSS) and multiple pregnancies. So, surgery with laparoscopic ovarian drilling (LOD) is often used before gonadotropins in order to obtain normal ovulatory cycles.